Use of biosolids from wastewater treatment plants and other organic fertilizers in agriculture—a preliminary results of a case study in banana cultivation in the Dominican Republic - Martínez Durán, Atuey J.; Rodríguez Núñez, Vladimir A.; Castillo Jáquez, José del C. (Frontiers in Water, 2023)
Introduction The use of biosolids from wastewater treatment plants in agriculture is considered relevant for the promotion of sustainable agricultural practices, the improvement of soil fertility, and the reduction of dependence on synthetic chemical products. The Dominican Republic is today the world's largest producer of organic bananas and the main exporter of organic and fair-trade bananas to Europe. The biosolids generated in the wastewater treatment plants in the Dominican Republic currently have no use. In other countries, biosolids are used for agriculture, although biosolids have different characteristics in each place and their potential must be analyzed. In the Dominican Republic, there is no research that analyzes biosolids and their impact on agriculture. This research aims to compare the nutritional composition of bananas in plantations fertilized with different doses of biosolids and other organic fertilizers. Methods For this test, five blocks were prepared with organic fertilization, another with potassium sulfate, and a control block. Laboratory analysis was used to determine the characteristics of the biosolids used and also to know the nutritional composition of bananas of the Williams variety. Results The results, when compared, show the impact that each of these fertilizers has or can have on the production of organic bananas in the Dominican Republic. Discussion The use of dose Y of the biosolid, characterized by the application of 16 kilograms of biosolid per plant, is the most recommended to fertilize the banana since the collected fruits presented the most optimal nutritional values.